Adherence to denosumab therapy and all-cause mortality in dialysis patients with osteoporosis: a retrospective cohort exploratory study - Chen, Ying-Chou; Chen, Jia-Feng; Yu, Shan-Fu; Hsu, Chung-Yuan; Chiu, Chien-Hua (Frontiers in Pharmacology, 2026)
BackgroundDialysis patients have a high risk of osteoporosis, leading to increasedfracture and mortality rates. Denosumab is commonly used in thispopulation due to its lack of renal accumulation, but its long-termbenefit depends on sustained adherence. This This exploratory study investigated therelationship between denosumab adherence and all-cause mortality indialysis patients with osteoporosis.MethodsThis retrospective case--control study included 1,200 hemodialysis patients. Four hundred deceased patientswere matched 1:3 by age, sex, and follow-up duration to 1,200 survivingcontrols. Adherence to denosumab therapy was calculated, and itsassociation with mortality was assessed using Cox regression analysis.ResultsAmong 401 denosumab-treated patients, 12 died and 389 survived duringfollow-up. The deceased group was older than survivors (85.0 ± 11.07 vs.75.87 ± 10.24 years, *p* = 0.016). Poor adherence occurred in 50% ofdeceased patients versus 7.5% of survivors (*p* <0.001).Comorbidities, including diabetes, hypertension, rheumatoid arthritis, liver disease, pulmonary disease, and cancer, differed significantlybetween groups. In Cox regression analysis, older age (HR = 1.137, 95%CI = 1.044–1.239) and poor adherence (HR = 0.065, 95% CI = 0.015–0.288) were significantly associated with higher mortality.ConclusionGood adherence to denosumab therapy was associated with lower all-causemortality risk in dialysis patients withosteoporosis. Improving treatment adherence may enhance survival in this high-risk population. Given the exploratory nature of this study and the limited number of events, these findings require validation in larger cohorts.